Dupilumab effectively and rapidly treats bullous pemphigoid by inhibiting the activities of multiple cell types - Yan, Tianmeng; Xie, Yinghan; Liu, Yuhua; Shan, Ying; Wu, Xiaoyan; Wang, Jing; Zuo, Ya-Gang; Zhang, Zhenying (Frontiers in Immunology, 2023)
Background: Bullous pemphigoid (BP) is an autoimmune skin-blistering disease. Systemic corticosteroids remain the first line treatment for moderate-to-severe BP with the potential for severe adverse events. Dupilumab has emerged as an alternative option for BP patients.Objective: We evaluated the efficiency and safety of dupilumab on BP treatment and explored a mode of drug action in depth.Methods and Results: A multicenter retrospective cohort included 20 BP patients who received dupilumab with or without systemic corticosteroid in dupilumab group, and 20 matched BP patients who received corticosteroid alone in conventional group. Serum samples were collected from 20 patients (10 from dupilumab group and 10 from conventional group) at baseline and week 4. Compared to systemic corticosteroid alone, dupilumab with or without systemic corticosteroid was similarly efficacious in clinical remission at week4 (complete remission plus partial remission: 100%) and week24 (complete remission plus partial remission:100%), but allowing significant decreases in the cumulative doses of corticosteroids with reducing the incidence of adverse events. However, dupilumab did not decrease BP180 antibody despite an obvious clinical improvement. Comparative plasma proteomic analysis performed before and after treatment in 3 BP patients from dupilumab group revealed that drug use was associated with 30 differentially expressed proteins, including 26 down-regulated and 4 up-regulated proteins.The former consisted of immune related proteins involved in T/B cell interactions (inducible Tcell co-stimulator ligand, ICOSL) and in the activation of eosinophils (PRG2), mast cells (S100A12), and complement (CR2). TARC and ICOSL levels correlated with BP severity in patients who received either dupilumab or conventional treatment.Conclusions: Dupilumab has similar efficacy in treating BP as conventional drugs, by inhibiting the activities of many types of immune cells and complement, and regulating the interactions between T and B cells.